Islamic finance: multicriteria analysis and application. (13th September 2019) - Jmili, Nesrine
Several studies and researches are interested in Islamic finance; these studies seek to understand the concept, to identify the principles, the operations and to join the experiments. The purpose of this paper is to determine a comparative study between Islamic banks and conventional banks in terms of performance. This article deals with multicriteria analysis in order to offer a model that makes it possible to clearly explain the ranking randomness of banks, how to take into account actors' behaviours from inter-criteria and intra-criteria information. In addition, we make a strong impression on a robustness review of our empirical analysis.